Research on the Influence of Moisture Condition on the Mechanical Properties and Microstructure of Sandstone - Zuosen. Luo; Zuoxiang. Zhu; Hao Bai; Daxiang Liu; Qiancheng. Sun (Shock and Vibration)
The sandstone from the dry to saturated state shows obvious deterioration characteristics. Taking the sandstone of a slope in the Three Gorges Reservoir area as the research object, uniaxial/triaxial compression of sandstone samples with different water-bearing states (dry, natural, and saturated) is carried out to study the changes in macromechanical properties of sandstone under different water-bearing states. Combined with NMR and SEM, the characteristics of microstructure of sandstone under different moisture conditions were studied. The results show that, with the increase of water content, the macromechanical parameters of sandstone gradually decrease, and the fine and microstructure characteristics are characterized by the gradual increase in the number of pores and the gradual increase in pore size. Based on the PFC2D software, considering the weakening effect of water on the partial cementation from a mesoscopic point of view, it is proposed to use soft and hard contacts to simulate the changes in the degree of cementation between particles under different water-bearing conditions and to study the impact of sandstone micromechanical parameters with changes in water content. Related research results can provide theoretical guidance for the stability evaluation of wading rock mass engineering.